Towards the Subject of Psychopedia and Human Education - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2000)
In this article there are some foundations to a new scientific subject of educology named psychopedia. The main goal of this subject is to research technology for the training of high quality psychological and mental culture.